The Transformation of Islamic Educational Institutions and Curricula in the Indonesian Archipelago During the Dutch and Japanese Colonial Periods: An Islamic Ethnopedagogical Perspective - Thahirrah, Al Athiyyah; Iswantir, Iswantir; Kasmawati, Erni; Yusnaidi, Rizki Illahi; Novia, Ardila (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the transformation of the Islamic curriculum in the Indonesian archipelago during the Dutch and Japanese colonial periods. The study focuses on the influence of colonial policies on the direction, structure, and content of the curriculum in Islamic boarding schools, prayer rooms, and madrasas, as well as the role of Islamic ethnopedagogy in preserving the character of Islamic education based on tradition and local wisdom. Methodology: This study uses a qualitative-historical approach with heuristic, source criticism, interpretation, and historiography stages. Data were obtained from colonial archives, education regulations, curriculum documents, textbooks, and national and international scientific journals. All sources were described in a historical-critical and ethnopedagogical manner to identify changes in the objectives, structure, content, and value orientation of the Islamic education curriculum in the colonial socio-cultural context. Main Findings: The results show that Dutch colonial policy was repressive and restricted Islamic educational institutions and curricula, while Japan was more cooperative, albeit oriented towards the interests of the war. These differences in policy led to significant changes in institutional structure and curriculum content. In this context, Islamic ethnopedagogical values based on local traditions played an important role in maintaining the Islamic identity of the archipelago's communities. Novelty/Originality of this study: This study is unique in that it places the Islamic education curriculum as the main focus of analysis in the colonial context using an Islamic ethnopedagogy approach. Unlike previous studies that emphasized institutional aspects or colonial policies, this study shows the integration of local Islamic cultural values in the curriculum as a strategy for pedagogical adaptation and resistance, as well as its contribution to the development of a local wisdom-based Islamic curriculum.